CURRENT PROGRESS IN SYNTHESIS AND PROPERTIES OF DOPED BISMUTH TITANATE FOR ADVANCED ELECTRONIC APPLICATIONS - Al-Amani, Umar (Nova Science, 2012)
Lead-free bismuth-layered compounds have been widely studied as alternative materials for advanced electronics applications such as ferroelectric random access memories (FRAM), piezoelectric applications, electro-optic devices, micro-sensors,micro-elecho-mechanical systems, actuators, transducers and capacitors Lead-free bismuth-based materials have been chosen to overcome the toxicity issue produced from lead-based compounds. Various methods have been used to produce bismuth-layered compounds such as solid state reaction, hydrothermal, sol gel and soft combustion techniques. All of these techniques have advantages and disadvantages. In early stage, Bi4Ti3O12 (BIT) has been widely studied. However, serious issues of low remanent polarization, high leakage current, low fatigue resistance and high processing temperature are obstacles to practical applications. Therefore various dopants have been used to modify the properties. This review describes the progress in the synthesis of BIT using various methods. The effects of dopants on properties of BIT are also explained. Selected applications of the cornpounds are also discussed.